Analysis of Resilience and Leadership on the Commitment to the Implementation of Electronic Medical Records - Puspita, Mariana; Wardani, Ratna; Ellina, Agusta Dian (Chakra Brahmanda Lentera Institute, 2024)
Background: Healthcare facilities, particularly hospitals, must deliver swift, precise, and reliable medical services. Additionally, all healthcare providers are mandated to implement electronic medical records as part of their service delivery. Quality services can be good if the patient's medical records are complete, fast, and precise in providing information for health services. Implementing the electronic medical record system ensures resilience, leadership, and commitment. The study aimed to analyze the factors that influence resilience policies on the commitment of the electronic medical record system at the Muhammadiyah Siti Khodijah Hospital. Methods: The quantitative research method uses a cross-sectional design. The population is all Hospital Employees. The sample is 125 employees, and the sampling technique uses Proportional Random Sampling. Independent Variables Resilience and Leadership, Independent Variable Commitment. The instrument used is a questionnaire with a Likert scale. Statistical tests use multiple linear regression Results: The results of the resilience study (X1) have an influence on commitment (Y) with (p = 0.000) < 0.05, and leadership (X2) has an impact on commitment (Y) with (p = 0.000) < 0.05, and the Adjusted R Square value is 0.935 or 93.5%. Conclusion: There is a relationship between resilience and leadership variables and commitment. Employee resilience needs to be improved to maintain the quality of policies and commitments in working. Good leadership will support the Commitment of each employee.